The Relationship between fiber diameter and performance of yak wool (Mongolian Journal of Agricultural Sciences, 2021)
This article demonstrates the thermal sensitivity and conductivity as well as the water permeability and absorptivity of Mongolian yak wool surfaces according to the Kawabata evaluation method. According to the results of the study, the mean value of thermal sensitivity (Qmax) of yak wool surface is 0.051 w/cm2 for down and 0.061 w/cm2 for coarse hair while the mean value of thermal conductivity is 2.08x10-4 (cal/cm ·0C) for down and 2.63x10-4(cal/cm · 0C) for coarse hair.This study, with its high level of confidence (p = 0.05), proves the difference between down and coarse hair. Additionally, the study shows a strong correlation between the thermal conductivity and the fiber diameter of Mongolian yak wool, resulting in a correlation level of r = -0.80 for down and r = 0.86 for coarse hair.  When measuring the wettability of Mongolian yak wool, yak wool surface exhibited waterproof properties with a contact angle of 146.50 degrees for down hair and a contact angle of 147.10 degrees for coarse hair. The study also revealed a low correlation level of r = 0.39 for down and r = 0.40 for coarse hair when examining the relationship between the contact angle and the diameter of yak wool.